VeggieTales. Holiday double feature [videorecording (DVD)] (Big Idea's VeggieTales., 2004)
In the Star of Christmas, it's 1880's London and Cavis and Millward are putting the finishing touches on their first Christmas musical. Filled with spectacle and more electric lights than London has ever seen. Unfortunately, a church pageant is opening the same night, right down the street, featuring a priceless artifact that hasn't been seen in 80 years! Just how far will Cavis go to make sure his show opens on top? Find out in this hilarious, action-packed adventure which teaches that it's the true story of God's love that shows us how to love one another - at Christmas time and throughout the year. In the Toy that saved Christmas, the unscrupulous toy maker, Wally P. Nezzer, appears in his own TV commercials and has convinced all of Dinkletown that "Christmas is when you get stuff!". With the town's children begging for more toys, it's sure to be the worst Christmas ever - that is until one brave little Buzz-Saw Louie doll decides to take matters into his own hands!